Projection Group Decision-making Model of Water Conservancy Project Emergency Plans Based on Interval Intuitionistic Fuzzy Information - CAO Xiongfeng; XIE Wenjing; FENG Jiwei (Renmin Zhujiang)
To deal with the group decision-making of emergency plans more accurately and efficiently,this paper proposes a group decision-making model of emergency plans based on interval intuitionistic fuzzy information and projection method,since the decision information with zero value in the aggregation operators will get inaccurate results.First,the interval intuitionistic fuzzy set theory and projection method are utilized to build a multi-objective optimization model to solve the optimal aggregation information of the group.Then,the interval intuitionistic fuzzy entropy is adopted to determine the attribute weight of the index,and the closeness based on the project projection is employed to determine the optimal plan.Finally,the effectiveness of the decision-making model is verified by case analysis.The research results show that the social impact of disasters and the aftermath treatment play an important role in emergency decision-making;the projection decision-making model improves the accuracy and efficiency of the decision-making process and has good applicability and generalization.